The synthesis and degradation of collagenase-degradable poly(2-hydroxyethylmethacrylate)-based hydrogels and sponges for potential applications as scaffolds in tissue engineering - Paterson, S.; Shadforth, A.; Brown, David; Madden, P.; Chirila, T.; Baker, M. (Elsevier Science, 2012)
A collagenase-cleavable peptide-based crosslinking agent was synthesized and was incorporated into PHEMA sponges, and P[HEMA-co-MeO-PEGMA] gels and sponges [HEMA 2-hydroxyethyl methacrylate, PHEMA = poly(2-hydroxyethyl methacrylate), MeO-PEGMA=poly(ethylene glycol) monomethyl ether methacrylate]. PHEMA and P[HEMA-co-MeO-PEGMA] sponges had polymer droplet morphologies where the dimensions of the morphological features were three to five times larger compared to sponges that were crosslinked with tetraethylene glycol dimethacrylate (TEGDMA), while the P[HEMA-co-MeO-PEGMA] gels had similar morphologies regardless of the crosslinking agent. The differences in the dimensions of the morphologies of the sponges were attributed to differences in hydrophilicities of the crosslinking agent. When incubated in a collagenase solution, PHEMA sponges did not degrade, but P[HEMA-co-MeO-PEGMA] gels took 28 days to degrade and the P[HEMA-co-MeO-PEGMA] sponges took 101 days to degrade to 8% dry weight remaining. A cytotoxicity assay showed that the hydrogels do not elicit any cytotoxic response in vitro.